2015
DOI: 10.1016/j.bmc.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective and stereospecific hydroxylation of GR24 by Sorghum bicolor and evaluation of germination inducing activities of hydroxylated GR24 stereoisomers toward seeds of Striga species

Abstract: Bioconversion of GR24, the most widely used synthetic strigolactone (SL), by hydroponically grown sorghum (Sorghum bicolor) and biological activities of hydroxylated GR24 stereoisomers were studied. Analysis of extracts and exudates of sorghum roots previously fed with a racemic and diastereomeric mixture of GR24, using liquid chromatography-tandem mass spectrometry with multiple reaction monitoring (MRM), confirmed uptake of GR24 and suggested its conversion to mono-hydroxylated products. Two major GR24 metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…3) will decrease the activities of exogenous SLs, since the activities of HO-SLs were lower than those of deoxy-SLs on the inhibition of shoot branching in rice 35) and the induction of seed germination against Striga hermonthica. 36) The production of endogenous SL was little inhibited by the administration of deoxy-SLs in both the red bell pepper and the sunflower. This result implies the possibility that hydroxylation of exogenous deoxy-SLs is a metabolic reaction distinct from endogenous SL biosynthesis.…”
Section: Discussionmentioning
confidence: 95%
“…3) will decrease the activities of exogenous SLs, since the activities of HO-SLs were lower than those of deoxy-SLs on the inhibition of shoot branching in rice 35) and the induction of seed germination against Striga hermonthica. 36) The production of endogenous SL was little inhibited by the administration of deoxy-SLs in both the red bell pepper and the sunflower. This result implies the possibility that hydroxylation of exogenous deoxy-SLs is a metabolic reaction distinct from endogenous SL biosynthesis.…”
Section: Discussionmentioning
confidence: 95%
“…published 3′‐methyl‐GR24 having an EC 50 value one order of magnitude higher than that of GR24 on P. ramosa and comparable with GR24 for O. minor . Several hydroxylated analogues of GR24 showed germination‐stimulating activity at 0.1 μ m , but results at lower concentrations were not tested …”
Section: Resultsmentioning
confidence: 99%
“…51 Several hydroxylated analogues of GR24 showed germination-stimulating activity at 0.1 μM, but results at lower concentrations were not tested. 52 Pest Manag Sci 2019; 75: 3113-3121 © 2019 The Authors.…”
Section: Bioassaysmentioning
confidence: 99%
“…Given that this tricyclic intermediate can be synthesized in 55% yield following route A in Scheme 10, the global yield for synthesis of 28 is 4.4% (1.8% in the case of 29). In a subsequent study, 28 showed activity in the germination of S. hermonthica (but only limited activity for Striga gesnerioides), and was found to be more active than the GR24 analogue epimer at C-4 (Ueno et al 2015). Similarly, the study by Malik et al (2011) presents the synthesis of similar analogues hydroxylated or acetylated at C-4, as well as others containing a ketone group.…”
Section: Gr24 Familymentioning
confidence: 92%
“…After butenolide ring addition, the two analogues PLN655 and PLN655a were obtained in 43% and 48% overall yield respectively. The former, together with its nonnitrogen-containing derivative PLC655, which was also synthesized, were tested on O. aegyptiaca as racemates and their activity levels found to be higher than those for GR24: both were highly active at 10 -4 and 10 -6 M, with percentages of around 80-90%, and PLN655 retained this level down to 10 -8 M. Ueno et al (2015) synthesized the GR24 analogues monohydroxylated at each aromatic position of the A-ring (C-5, C-6, C-7 or C-8; Scheme 19). The starting materials in this case were four hydroxylated indan-1one derivatives isolated from root exudates of hydroponically grown Sorghum bicolor.…”
Section: Gr24 Familymentioning
confidence: 99%